Evolutionary optimization of spare parts inventory policies: a life cycle costing perspective - Duran, Orlando (2019)
This paper proposes the development of an optimization model for spare parts management during the life cycle of a physical asset. The main characteristic of the proposed model is that it is based on the principles of Activity Based Costing (ABC). The aim of this model is to allow decision makers to perform an optimal inventory policy and the correspondent parameter definitions for a series of spare parts. The model is optimized through the use of a Genetic Algorithm. A hypothetical case study is presented and discussed. (C) 2019, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.